Optimización y simulación dinámica de la especie carachi (Orestias agassii) para el manejo sostenible de la pesca en el lago Titicaca - Calsín Quispe, Giovana (2004)
Three models are developed to analyze fishing of the carachi species in Lake Titicaca (Peru-Bolivia). Using the Bioeconomic Model, in the stationary state, the reference points are found for the maximum sustainable return (MSR), the maximum economic return (MER) and free access (FA). The average current extraction rate (X) and the human effort involved (E) in exploiting this resource are 2,216 tons per annum and 8,857 fishermen respectively. These are higher than the optimal values for the MER (1 ,599 tons per annum and 3,016 fishermen) in maintaining a biomass of 19,207 tons. The dynamic model based on the optimal control theory indicates that the levels of the stationary state are sensitive to changes in the price and unit extraction cost parameters. Using the dynamic programming model, optimal values are estimated for different levels of available stock, stable over the long term, that oscillate between 1,160 and 2,320 tons.